THE IMPACT OF ZAKAT ASSISTANCE ON THE ACADEMIC PERFORMANCE OF ASNAF IN PERLIS - Ernie Adnan; Roziah Ramli; Naziroh Ibrahim, (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2025)
This study investigates the impact of zakat assistance on the academic performance of Asnaf students in the state of Perlis. Grounded in the objective of evaluating the influence of zakat aid on academic outcomes, the study addresses the central research question: What is the impact of zakat assistance on the academic outcomes of Asnaf students? A quantitative research design was employed, and data were collected through a structured questionnaire distributed via Google Forms to a sample of 155 Asnaf students from three selected primary schools in Perlis. The findings reveal a positive correlation between the zakat assistance received and the students’ academic performance. Specifically, students who reported receiving consistent zakat support demonstrated improved academic results, higher motivation, and greater school engagement compared to their peers who received minimal or no assistance. The study suggests that zakat assistance, when allocated effectively, plays a significant role in supporting the educational development of underprivileged students by alleviating financial burdens and providing access to learning resources. These findings underscore the importance of continuous and well-managed zakat distribution to enhance educational equity and contribute to the broader goal of social upliftment among the asnaf community. The study concludes by recommending further research to explore the long-term effects of zakat assistance on academic and socio-economic outcomes across different educational levels.